Humanized mouse as an appropriate model for accelerated global HIV research and vaccine development: current trend. (1st November 2016) - Ibeh, Bartholomew Okechukwu; Furuta, Yasuhide; Habu, Josiah Bitrus; Ogbadu, Lucy
Abstract: Humanized mouse models currently have seen improved development and have received wide applications. Its usefulness is observed in cell and tissue transplant involving basic and applied human disease research. In this article, the development of a new generation of humanized mice was discussed as well as their relevant application in HIV disease. Furthermore, current techniques employed to overcome the initial limitations of mouse model were reviewed. Highly immunodeficient mice which support cell and tissue differentiation and do not reject xenografts are indispensable for generating additional appropriate models useful in disease study, this phenomenom deserves emphases, scientific highlight and a definitive research focus. Since the early 2000s, a series of immunodeficient mice appropriate for generating humanized mice has been successively developed by introducing the IL-2Rγ null gene (e.g. NOD/SCID/γc null and Rag2 null γc null mice) through various genomic approaches. These mice were generated by genetically introducing human cytokine genes into NOD/SCID/γc null and Rag2 null γc null mouse backgrounds. The application of these techniques serves as a quick and appropriate mechanistic model for basic and therapeutic investigations of known and emerging infections.